2015
DOI: 10.1007/s00256-015-2179-4
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variation in classification of malleolar fractures

Abstract: Classification according to the classical systems showed moderate interobserver agreement, probably due to an unclear trauma mechanism or the difficult relation between the level of the fibular fracture and syndesmosis. Substantial agreement on posterior malleolar fractures is mostly due to small (<5 %) posterior fragments. A classification system that describes the presence and location of fibular fractures, presence of medial malleolar fractures or deep deltoid ligament injury, and presence of relevant and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…Another important limitation concerns the measurement of posterior malleolar fragment size on lateral preoperative X-rays and the measurement of postoperative step-off on lateral X-rays. Some articles that were published in the last few years have reported that the interobserver agreement of fragment size on lateral X-rays is poor [29, 30] and even CT-scanning is not reliable to compare different fragment sizes [22, 23]. Therefore, the possible relation between fragment size and functional outcome may have been missed in our study because of inaccurate measurements.…”
Section: Discussionmentioning
confidence: 86%
“…Another important limitation concerns the measurement of posterior malleolar fragment size on lateral preoperative X-rays and the measurement of postoperative step-off on lateral X-rays. Some articles that were published in the last few years have reported that the interobserver agreement of fragment size on lateral X-rays is poor [29, 30] and even CT-scanning is not reliable to compare different fragment sizes [22, 23]. Therefore, the possible relation between fragment size and functional outcome may have been missed in our study because of inaccurate measurements.…”
Section: Discussionmentioning
confidence: 86%
“…Future studies should only use CT scans when assessing articular congruency. 16 Another limitation is that only trimalleolar fractures which were fixed using a posterolateral approach are included. There are no data available on unfixed posterior malleolar fragments or those treated with 'anterior to posterior' percutaneous fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Na literatura encontramos trabalhos que avaliaram a variação na classificação intra e entre observadores das fraturas de tornozelo. Todos os estudos encontrados utilizaram o coeficiente Kappa para a análise da concordância, mostrando-se o mais confiável para se fazer a pesquisa (18)(19)(20)(21)(22)(23) . Na literatura brasileira foram encontrados quatro estudos que fizeram uma análise semelhante (7,12,24,25) .…”
Section: Discussionunclassified
“…O grande problema da classificação de Lauge-Hansen é que em muitos casos não se consegue, ao certo, concluir o mecanismo de trauma que gerou a fratura (26) . As classificações de Danis-Weber e AO-OTA têm como dificuldades a definição da posição da sindesmose tibiofibular e a impossibilidade de classificação das também fraturas isoladas do maléolo medial (23) . A classificação da AO-OTA não é muito utilizada na prática clínica, por apresentar muitos subtipos (9 possibilidades) o que dificulta sua memorização e utilização no contexto de unidades de urgência/emergência.…”
Section: Discussionunclassified